ANALISIS KEMAMPUAN LABA, PIUTANG, PERSEDIAAN, BIAYA ADMINISTRASI & PENJUALAN, DAN RASIO LABA KOTOR TERHADAP PENJUALAN DALAM MEMPREDIKSI LABA - Abubakar Arif; Eka Rudiyaningsih (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2008)
This thesis is to examine capability of net income, account receivable, inventory, operating expense and gross profit margin ratio to sales in predict of net income to the next year. Financial information is getting from financial statement of 35 manufacture companies that listed in Bursa Efek Jakarta (BEJ) of the year 2004-2006. Analized of data using Multiple Regression Analysis. The result of this research is to feature of net income, account receivable, operating expense and gross profit margin ratio to profitable in predict of net income of the next year. Partially, only net income that have significant influence to net income of the next year.